Analyzing the Agrarian Conflict Between Administrative Court and General Court - Andre Irwanda; Fauzie Yusuf Hasibuan; Maryano (International Journal of Educational Research Excellence (IJERE), 2023)
Agrarian conflicts weakened the Administrative Judiciary and General Judiciary sectors in their settlement. The number of agrarian cases according to the Consortium for Agrarian Renewal for the period 2010-2019 amounted to 3,358 cases. The plantation, property, and infrastructure sectors become the largest agrarian conflicts in the last 5 years.  Normative juridical research methods, statutory approaches and case studies, primary and secondary legal materials with analysis and technical descriptive analysis. So the author analyzes the Urgency of the Establishment of Agrarian Courts. The results of the study assessed that the judicial power is free without outside intervention. The type of court chamber has not been able to solve problems in the land sector properly. An Agrarian Court is needed as an effort to resolve land problems and reduce blur in the authority to file cases. The administrative court and the general court have a jurisdiction to handle and settle agrarian conflict. The jurisdiction of administrative court is in the administrative aspect while the jurisdiction of general court is in the rights aspect. With high percentage of agrarian cases unsettled, there is a need to establish agrarian court to expedite the settlement of agrarian case comprehensively.